DESAIN DAN IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS MOBILE LEARNING MENGGUNAKAN MOODLE MOBILE APP - Agariadne Dwinggo Samala; Bayu Ramadhani Fajri; Fadhli Ranuharja (Universitas Negeri Padang, 2019)
The purpose of this study is to produce instructional media of ICT guidance based on Mobile Learning using Moodle Mobile App that is valid, practical, and effective. This type of research is Research and Development (R & D). The development model used is the ADDIE model. The experimental method used Intact-Group Comparison. The sample was students of class X at SMA Negeri 1 Sungai Geringging. The instrument was validation questionnaire to measure validity, response questionnaires to measure the practice, and post-test questions of multiple choice to measure the effectiveness of developed media. The results showed that media declared valid by the validator assessment, and practically use by teachers and learners. Percentage of classical completeness at experiment group reached 87,5%, and 12,5% for classical incompleteness. While the control group reached 25% for classical completeness, and 75% for classical incompleteness. It means that ICT guidance media based on Mobile Learning using Moodle Mobile App is